Implementasi Program Transformasi Perpustakaan Berbasis Inklusi Sosial Berdasarkan Key Performance Indicator (KPI) di TBM Teras Literasi Mutiara Langit Biru - Dzakkiyah Addawiyah Marpaung; Franindya Purwaningtyas (Universitas Sebelas Maret Library, 2025)
This study aims to analyze the implementation of the Social Inclusion-Based Library Transformation Program (TPBIS) at the Community Reading Center (TBM) Teras Literasi Mutiara Langit Biru, based on four key indicators of the Key Performance Indicator (KPI): enhancement of information services, community engagement, advocacy, and promotion and publication. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that TBM Teras Literasi Mutiara Langit Biru has successfully provided inclusive information services through collection development and the use of technology, and has actively involved children in various literacy activities. Advocacy strategies were primarily carried out through non-financial efforts and collaborations with partner institutions, while promotion and publication were focused on online media. The program has had a positive impact on improving literacy, strengthening social interaction, and empowering the community in a sustainable manner.